A hybrid model for estimation of ground movements due to mechanized tunnel excavation. (5th March 2019) - Zhao, Chenyang; Hölter, Raoul; König, Markus; Alimardani Lavasan, Arash
Abstract: To provide realistic predictions of mechanized tunnel excavation‐induced ground movements, this research develops an innovative simulation technique called hybrid modeling that combines a detailed process‐oriented finite element (FE) simulation (submodel) with the computational efficiency of metamodel (or surrogate model). This hybrid modeling approach has three levels. In Level 1, a small scale submodel is cut out from the global model and the continuous simulations are conducted in this submodel. Level 2 deals with identification of uncertain soil parameters based on the measurements (e.g., surface settlements) during tunnel excavation. In Level 3, the tunneling process parameters (e.g., grouting pressure) can be optimized to control tunneling‐induced ground movements or building deformations according to the design criterion. The proposed hybrid modeling approach is validated via a 3D numerical simulation of mechanized tunnel excavation. The results show the capability of the proposed approach to provide reliable model responses in the near field around the tunnel with reduced computational costs.